Management Auditing: Controlling Food and Beverage Costs at The Oberoi Bali Hotels - A A M Y Fitri; I B A Yasa; I N Mandia (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
This study examines the effectiveness and efficiency of controlling food and beverage costs and reveals findings obtained during the management audit, so that appropriate recommendations can be given for better company’s performance in the future. The analysis technique uses quantitative and qualitative descriptive. Data sources are primary and secondary data obtained through observation, interviews, documentation and questionnaires. This study shows that food and beverage costs are still above the company's standards, so that effectiveness and efficiency can’t be achieved. Companies need to supervise the purchase of raw materials, use entertainment fees, and food spoiled so that food and beverage costs can be controlled properly. In addition, food and beverage sales must be increased in order to meet sales targets, so as to provide maximum benefits for the company.